The influence of executive function therapy on improving social maturity in children with Attention Deficit Hyperactivity Disorder (ADHD): An experimental study - Hidayat, Taufik; Imadduddin, Imadduddin; Al-Hendawi, Maha; Al Afghani, Abdullah Azzam (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2024)
Children with Attention Deficit Hyperactivity Disorder (ADHD) have non-adaptive behavioral problems related to social maturity, which impact their future lives as adults, thus necessitating access to appropriate treatment. This experimental study aims to examine the effect of executive function therapy on improving social maturity in children with ADHD. It adopts a comprehensive approach, employing a one-group pretest-posttest design on 20 children with ADHD. The social maturity scores of the children in the initial examination ranged from 32 to 86, measured using the Vineland Social Maturity Scale (VSMS), and then analyzed by one-way repeated measures ANOVA using SPSS. The results show an improvement after executive function therapy (Phase III/Post-test, M = 75.90; Phase II, M = 64.00; Phase I, M = 64.30; Pre-test, M = 61.35), thus indicating a significant influence of the therapy on the improvement of the social maturity of children with ADHD, F(3; 16) = 73.9; p < .001, η_p2 = .795 showed moderate level of therapy effectiveness. This study suggested that executive function therapy is effective in improving social maturity in children with ADHD.